Manobras evasivas subótimas em leo sujeitas à força de arrasto atmosférico e a colisões com detritos espaciais - Oliveira, Eduardo Mendes (2016)
In this research we studied evasive maneuvers to avoid collisions in an environment with debris, enabling missions to the space. When a collision occurs, usually the space vehicle is completely damaged and destroyed, thus ensuring that the satellite avoids this collision will preserve the objective of the mission. In this study, we will see how a space vehicle can perform an evasive maneuver through thedriveline under the effect of the atmospheric drag force, whose efficiency will be established through the settings of technological parameters, which are the amount of fuel in the space vehicle and the ability to eject the propellant through the propulsion system. The purpose of the evasive maneuver is to avoid the collision but to keep the vehicle in its nominal orbit. At first we found several initial conditions of collision with the space vehicle under the influence of Earth's gravitational force, to ensure that there would be a collision between objects, from that on, the propulsion force was applied, after that, considering only the effect of atmospheric drag on the objects and right after the two collisional objects were brought under the effect of both forces, the force of the atmospheric drag and the propulsion together. In search of the most economical maneuver, from the point of view of fuel consumption, maneuvers were performed with lower propulsion drive time, and at different times of the trajectory of the vehicle and also at random times with the use of the propulsion force . The maneuvers were found through numerical simulations for each mathematical model of disturbances added to the orbital dynamics under the influence of the gravitational force.